The Use Of Accounting Information Systems For Micro, Small And Medium Enterprises (MSMEs In The City Of Makassar) - Rina Andriany; Nilan Pradana; Nurhalisa Ramadhan; Muh Khalid Nurqadri; Linda Razak (International Journal of Economic Research and Financial Accounting, 2023)
The purpose of this study is to determine the factors that influence the use accounting information on MSME actors in Makassar .The independent variables in this study are accounting knowledge, business experience, work motivation, education level and business scale. While the dependent variable is the use of accounting information. Deep data collection methods this study using simple random sampling, obtained sample 30 .data collection method in this study using questionnaire. This study uses statistical data analysis techniques regression with the help of SPSS. The results of this study indicate accounting knowledge business experience, work motivation, education level, and business scale positive effect on the use of information accountant. There are still other independent variables that can influence the use of accounting information that were not examined in this study. Future research agendas are suggested to extend a longer observation period to get better results and add research variables that influence the use of accounting information.